Self-Reported Sobriety Labels: Perspectives from Alumni of Inpatient Addiction Treatment - Bourdon JL; Judson S; Fields T; Verdecanna S; Vadhan NP; Morgenstern J (Dove Medical Press, 2024)
Jessica L Bourdon,1 Sidney Judson,1 Taylor Fields,1 Sabrina Verdecanna,1 Nehal P Vadhan,2 Jon Morgenstern3 1Wellbridge Addiction Treatment and Research, Calverton, NY, USA; 2Institute of Behavioral Science, Feinstein Institutes for Medical Research. Department of Psychiatry, Donald and Barbara Zucker School of Medicine at Hofstra/Northwell, Hempsted, NY, USA; 3Department of Psychiatry, Donald and Barbara Zucker School of Medicine at Hofstra/Northwell, Hempsted, NY, USACorrespondence: Jessica L Bourdon, Email jbourdon@wellbridge.orgBackground: There is a lack of consensus in the addiction field as to how to refer to alumni of residential treatment who no longer use substances or who reduce their use. In the literature, this label and broader identity are typically discussed in technical (amount and frequency of use) or social terms (environment and social network changes).Objective: The current paper seeks to simplify the discussion by focusing on personal labels without complex technical or social considerations. Alumni of an inpatient addiction treatment facility were asked how they refer to themselves regarding their sobriety status post-discharge.Methods: Forty-nine patients were contacted 3 months post-discharge from a residential inpatient addiction treatment (men = 67%; Mage = 47.75 years). The patients completed a post-discharge assessment that was conducted by a trained research assistant over a 20-minute video call. The current study focused on a "sobriety label" measure in which patients indicated what they want to be called. Patients also explained why they chose their answer in an open-ended question.Results: Most patients identified as in recovery (n = 29; 59.18%) followed by a sober person (n = 7; 14.29%) and four other responses. No alum selected the in remission option, which is notably a common way to refer to patients who no longer use substances.Conclusion: The current study adds a critical patient/alumni perspective to the existing body of literature and serves as a call to action for researchers to add a similar "sobriety label" measure to future assessments, studies, and batteries in effort to bring consistency to the labels, definitions, and identities that are published. This methodology of understanding how this population identifies will create uniformity in future literature and decrease the stigma surrounding addiction.Plain Language Summary: There is a history of inconsistent use of labels, definitions, and identities in the addiction treatment field. Few past studies have directly asked patients how they self-label, and it is important to ask those who use substances or who have reduced their use what they preferred to be called. This study asked a simple question to alumni of an inpatient treatment facility what they want to be called. We then asked them to explain why they chose that answer. Most alumni identified as "in recovery" or "a sober person". This simple tool can be utilized by other facilities and also highlights that many research studies are referring to individuals by terms they do not prefer (eg, "in remission").Keywords: sobriety, identity, label, addiction, discharge, recovery, sober person, inpatient